Pemberian jus belimbing Demak (Averrhoe carambola I) berpengaruh terhadap penurunan tekanan darah sistolik dan diastolik pada penderita hipertensi - Heri Sulistiyono; Muflihah Isnawati (Jurnal Gizi Klinik Indonesia, 2011)
Backgrounds: Hypertension is the main risk factor for cardiovascular disease that is the primer cause of death in the world. Hypertension is associated with food pattern that is high in sodium and low in potassium. Demak’s starfruit  is a high potassium food that has negative effect on high blood pressure.Objective: To fnd out the effect of Demak’s starfruit juice for decreasing of systolic and diastolic blood pressure in patient with hypertension.Method: This study was randomized control trial (RCT) design in two groups. The frst group was treated with 500 ml Demak’s starfruit juice derived from 280 grams Demak’s starfruit containing 425 mg of potassium, 11 mg of calcium and 2,8 mg of magnesium for 7 days and the second group was a control with starfruit essence. The subjects in this study 34 persons. The subject had  systolic blood pressure 140 – 160 mmHg and diastolic 90 – 100 mmHg. Intake of sodium, potassium, calcium and magnesium during research was observed with 2 x 24 hour food recall method. Statistical analysis used here was Kolmogorov-Smirnov, paired t-test, independent t-test and anakova.Results: There was signifcant decreases in systolic and diastolic blood pressure of 19,71±7,39 and 14,41 ± 8,08 in treatment group with Demak’s starfruit juice, and decrease 4,41 ± 8,64 and 0,88± 6,67 in control group.Conclusion: Demak’s starfruit juice (Averrhoe carambola l) infuence on the decrease of systolic and diastolic blood pressure.